"It Would Be Nice to Know I'm Allowed to Exist:" Designing Ideal Familial Adolescent Messages for LGBTQ Women's Sexual Health. Issue 2 (3rd April 2021) - Rubinsky, Valerie; Cooke-Jackson, Angela
Abstract: Memorable messages, or messages people recall for a long period of time and identify as influential in identity development or behavioral assessment, provide a framework to address both adolescent advice and development and to identify areas that were absent from pivotal conversations like "the talk." In this qualitative survey study, we asked lesbian, gay, bisexual, transgender, and queer (LGBTQ) women to design the messages they wish their parents had provided about intimate health in their adolescence in light of the messages that they did receive. Findings suggest that ideal messages from parents would include a tone of positivity and affirmation, validation of diverse sexual and gender identities, and practical information about navigating changing bodies, sexual and reproductive health and contraception, as well as information about consent and negotiating sexual relationships. Although fewer, some participants believed these conversations are better suited for education systems and teachers than parents.